Job related stress and job satisfaction: a comparative study among bank employees - Elizabeth George and Zakkariya K.A (Journal of Management Development, 2015)
Purpose – The purpose of this paper is to examine whether job satisfaction and job-related stress differ among employees of different banking sectors. Design/methodology/approach – Questionnaire were administered to 337 employees from various banks belonging to private sector, public sector and new generation banks. One way ANOVA was conducted to find out whether job satisfaction and job relates stress varied on the basis of three different sectors of banks. Further post hoc test was conducted to find out which sector differs significantly. Findings – Results indicated that employees of different sectors of bank had different level of job satisfaction and job-related stress. Further it was revealed that public sector banks have lower job-related stress when compared to private sector banks and new generation banks; and higher job satisfaction when compared to new generation banks. Practical implications – With the rapid developments and competition in banks, measures should be taken in private sector banks and new generations banks to reduce job-related stress and enhance job satisfaction level of employees. This may also result in increased quality of services and reduced labour turnover in banks. Originality/value – The study is original and empirical in nature. It shows that the job satisfaction and job-related stress differ among employees of different groups of banks in the banking sector. If banking sector is considered as a true representative of the service sector, the results of this study has wider implication in the service industry as a whole.